Veterinary Medical School Admission Requirements (VMSAR) : 2019 Edition for 2020 Matriculation (Book collections on Project MUSE., 2019)
Fully up-to-date and packed with useful tips and helpful insights, this publication provides a comprehensive overview of the admission process for the national and international veterinary schools that are members of the Association of American Veterinary Medical Colleges (AAVMC). As the official guide to getting into vet school, it provides hundreds of pages of must-have information, essential to achieving your goal of becoming a veterinarian. The heart of this publication is a directory of member schools, providing the following information for each school: a summary of application procedures; requirements for application and residency; prerequisites for admission; deadlines for each component of the application process; a description of campus and campus life; and the costs of tuition and fees. Full-page spreads provide a complete profile of the different campuses and clearly lay out all the details you need to select the school that matches your needs best. Additional information includes an overview of the Veterinary Medical College Application Service (VMCAS); information about the accreditation of veterinary schools and professional licensure as a veterinarian; a helpful timeline for aspiring vets from high school onward; and firsthand accounts from current students and practitioners about what it's like to train as a vet. This publication provides concise, current, and the best comparative information for students interested in preparing for a career in veterinary medicine, as well as their advisors and counselors. It is the essential guide to becoming a DVM.